Dance Learning in Children with Special Needs Autism Pk-Plk Center at Extraordinary School (SLB) Cendana Pekanbaru City, Riau Province - Selvia Frety Yunia Enjelina; Agusti Efi (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
Eduction is a need of every human being, both normal and special needs, as stated in the national education system (Law No. 20 of 2003 article 5 paragraph (1) where it is stated that every citizen has the right to obtain a quality education, as a social creature human beings must be able to interact with their environment, especially with fellow humans. In carrying out this interaction, it also requires a medium of interaction in the form of communication both verbally (verbally) and non-verbally. The purpose of this research is how to describe the problems faced by teachers in teaching dance material to children with autism disorders at the SMALB level at the PK-PLK Center of SLB Cendana, Pekanbaru City, Riau Province. Also describes the strategies carried out by teachers in carrying out the learning process of dance material in children with Autism disorders, The research method used in this study is descriptive qualitative with the process of searching and compiling systematically based on (observation) interviews, compiling into a pattern of choosing data to be used as conclusions, collecting data on lesson problems faced by teachers in children with special needs, strategies and tips carried out by teachers and how teachers teach dance to children with special needs so that in this study add  understanding of learning and dealing with children with special needs at SMALB Sentra PK-PLK SLB Cendana Pekanbaru City, Riau Province.